ANALYSIS OF ROAD DAMAGE BASED ON THE BINA MARGA METHOD, SURFACE DISTRESS INDEX (SDI), AND PKRMS V.1.4.5 ON TLOGOWUNGU ROAD, PATI - Siti Nurhalisah; Kurnia Hadi Putra; Theresia Maria Chandra Agusdini (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2024)
This study aims to identify the types of road damage on Tlogowungu Road, Pati, within the section from Sta 0+000 to Sta 1+500. The study evaluates the road conditions and determines appropriate maintenance solutions using the Bina Marga 1990 method, which suggests that for segments 1, 2, 3, 5, 6, 9, 10, 11, 12, 13, and 14, routine maintenance is required, while periodic maintenance applies to segments 4, 7, 8, and 15. The priority ranking obtained after calculating the Average Daily Traffic (LHR) places the road in traffic class number 4, with a total average LHR of 500–2000 vehicles/hour, resulting in a UP value of 8. The SDI method indicates that routine maintenance should be performed on segments 1, 2, 3, 8, and 13, while periodic maintenance is required on segments 4, 5, 6, 7, 9, 10, 11, 12, 14, and 15. The results from the PKRMS software show that Tlogowungu Road has suffered significant damage, ranging from 50% to 100%. However, when rehabilitation is carried out, the road condition improves, with the percentage of the road in good condition increasing to up to 95%. Keywords: Road Damage, Surface Distress Index (SDI), PKRMS Software